Beyond the marrow: insights from comprehensive next-generation sequencing of extramedullary multiple myeloma tumors - Jelinek, T; Zihala, D; Sevcikova, T; Anilkumar Sithara, A; Kapustova, V; Sahinbegovic, H; Venglar, O; Muronova, L; Broskevicova, L; Nenarokov, S; Bilek, D; Popkova, T; et al. (Leukemia, 2024)
Extramedullary multiple myeloma (EMM) is an aggressive form of multiple myeloma (MM). This study represents the most comprehensive next-generation sequencing analysis of EMM tumors (N = 14) to date, uncovering key molecular features and describing the tumor microenvironment. We observed the co-occurrence of 1q21 gain/amplification and MAPK pathway mutations in 79% of EMM samples, suggesting that these are crucial mutational events in EMM development. We also demonstrated that patients with mutated KRAS and 1q21 gain/amplification at the time of diagnosis have a significantly higher risk of EMM development (HR = 2.4, p = 0.011) using data from a large CoMMpass dataset. We identified downregulation of CXCR4 and enhanced cell proliferation, along with reduced expression of therapeutic targets (CD38, SLAMF7, GPRC5D, FCRH5), potentially explaining diminished efficacy of immunotherapy. Conversely, we identified significantly upregulated EZH2 and CD70 as potential future therapeutic options. For the first time, we report on the tumor microenvironment of EMM, revealing CD8+ T cells and NK cells as predominant immune effector cells using single-cell sequencing. Finally, this is the first longitudinal study in EMM revealing the molecular changes from the time of diagnosis to EMM relapse.
Keywords: Bone Marrow; Humans; lidé středního věku; Biomarkers, Tumor; Multiple Myeloma; Female; mutace; Aged; senioři; lidé; mnohočetný myelom; nádorové biomarkery; ženské pohlaví; Male; Middle Aged; prognóza; kostní dřeň; Tumor Microenvironment; vysoce účinné nukleotidové sekvenování; nádorové mikroprostředí; High-Throughput Nucleotide Sequencing; Mutation; mužské pohlaví; Prognosis